Shellac and hydroxyapatitte coatings on titanium niobium and AISI 316L steel surfaces produced by dip-coating - Gomes, B. F.; Picon, C. A. [UNESP]; Fernandes, F. A P; Rodrigues Filho, U. P.; Tremiliosi-Filho, G. (The Electrochemical Society, 2012)
Shellac is a natural resin used for the preservation of fruits, bones and as a coating on drugs. The hydroxyapatite (HA), which is naturally found in human bones, is used as filler to substitute amputated bone or as a coating for prosthetics, promoting bone growth in implants of prostheses. The objective of this work is to immobilize HA from an alcoholic solution of shellac on plates of titanium, niobium and AISI 316L steel using the simple dip-coating method. The corrosion resistance of the uncoated films is compared with ones coated with shellac and shellac plus HA. The deterioration of the film composed of shellac with hydroxyapatite in saline solution follows the ascending order: AISI 316L steel, titanium, niobium. The elemental analysis of the shellac showed that it mainly consists of the elements C, H, N and O. We used the FT-IR spectrum to characterize the shellac and HA. ©The Electrochemical Society.
Keywords: Alcoholic solutions; Bone growth; Dip coating; Dipcoating methods; FT-IR spectrum; Human bones; Natural resins; Saline solutions; Bone; Corrosion resistance; Hydroxyapatite; Niobium; Prosthetics; Titanium; Coatings